The learners’ needs on local cultural contents of reading professional context textbook at English program study - Markus Deli Girik Allo; Nilma Taula’bi; Elim Trika Sudarsih (International Journal of Humanities and Innovation (IJHI), 2019)
Curriculum development comprises a process to meet learners’ needs leading to learners’ learning improvement. For that reason, curriculum developers should gather as much information as possible toward the learners’ needs. This study aims to reveal the learners’ needs on local cultural based-textbook in learning Reading Professional Context at the English department of Universitas Kristen Indonesia (UKI) Toraja, South Sulawesi, Indonesia. This study employed qualitative with survey design. One-hundred-and-fifty-five learners of English program study of UKI Toraja participated in this study. The instruments used in this study are questionnaire and semi structured-interview. The technique of analyzing data applied in this research is descriptive analysis in the form of calculation and percentage, and in analyzing the qualitative data (interview), we used cyclical data analysis. This study showed that the students’ need a learning objective to understand beliefs, norms, values, and social practices in Toraja for maintaining Torajan Culture and avoiding misunderstanding across the culture. This study also indicates that the students’ need themes about the cultural pattern in Toraja for learning materials include beliefs, values, norms, and social practices in Toraja. Besides, this study revealed that students’ need learning strategies and evaluation. Learning strategies are rooted in activities/exercises on the material content and the number of students. On-time evaluation is necessary during the process and at the end of the lesson.